Compact photobioreactor for Chlorella SP cultivation - Hang, Mun Fock (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Microalgae have attracted much interest for production of foods, bioactive compounds and especially their usefulness as fossil fuel substitute and energy alternative. In order to grow and tap the potential of microalgae in economic ways, compact photobioreactors are required. Although a good number of photobioreactors have been proposed, only a few of them can be practically used for mass production of microalgae. Besides, the growth rates of these microalgae are affected by factors such as temperature, pH, CO2, irradiance and different concentrations of nutrients. The characterization carried out allows improving the design and establishing the proper operating conditions for the production of microalgae. An alternative compact and appropriate photobioreactor is presented along with cultivation of chlorella sp to compare with normal laboratory chlorella sp cultivation. Cultivation begins with using chlorella sp microalgae seed from USM mixing with ratio with the Walnes Medium. The chlorella sp culture was then cultivated under normal laboratory scale and compact photobioreactor. UV-Vis spectrophotometer used to analyzed and follow the growth in chlorella sp cultures With the cultivation of cultures showing positive growth, the cultures being analyzed with UV-Vis spectrophotometer in order follow its growth in both normal conical flask and compact photobioreactor cultivation. With positive result of UV-Vis analysis for chlorella sp culture, a comparison was carried out in both conditions whereby compact photobioreator is proved better in cultivating the chlorella sp cultures.